A novel Xp11.22–22.33 deletion suggesting a possible mechanism of congenital cervical spinal muscular atrophy. Issue 3 (29th January 2021) - Liu, Jingwei; Wang, Kelai; Li, Baomin; Yang, Xiaofan
Abstract: Background: Congenital cervical spinal muscular atrophy (CCSMA) is a rare, nonprogressive, neurogenic disorder characterized by symmetric arthrogryposis and motor deficits mainly confined to upper extremities. Since its first proposal by Darwish et al. 39 years ago, only few cases have ever been reported. Vascular insult to the anterior horn of cervical spinal cord during fetal development was speculated to be the cause, however, the exact pathogenesis is still not well understood. Methods: In this study, whole‐exome sequencing (WES) and copy number variation (CNV) analysis were conducted on a definitive CCSMA patient, confirmed by the clinical manifestations and other supplementary examinations. Results: On physical examination, the patient was mainly characterized by symmetric, congenital, nonprogressive contractures, hypotonia, and muscle weakness mainly confined to the upper limbs, which were further supported by MRI and electromyography. Neuromuscular biopsy of the deltoid muscle demonstrated the type 1 myofiber predominance without any infiltration of inflammatory cells. The WES and CNV analysis unveiled a de novo Xp11.22–22.33 deletion. On further examination of the genes contained within this segment, we recognize UBA1 gene as the most likely pathogenic gene. Ubiquitin‐like modifier activating enzyme 1 is encoded by UBA1 gene (MIM 314370) located in Xp11.3 and is a critical protein that plays a vital role in ubiquitin‐proteasome system and autophagy. It is well documented that UBA1 gene mutation causes X‐linked infantile spinal muscular atrophy (XL‐SMA), which manifests phenotypes of arthrogryposis, hypotonia, and myopathic face. Type 2 XL‐SMA, which follows a nonprogressive and nonlethal course is very similar to the presentations of CCSMA. Conclusion: The phenotypic similarities between this CCSMA case and XL‐SMA prompt us to hypothesize a possible connection between UBA1 gene deficit and the pathogenesis of CCSMA. Our study is the first to demonstrate that CCSMA might have a genetic etiology, thus, expanding our insights into the underlying cause of CCSMA. Abstract : We report a female case of congenital cervical spinal muscular atrophy with Xp deletion. UBA1 on this deleted segment is highly associated with major clinical features of this patient. This is the first study with evidence that CCSMA may be linked to a genetic cause.